Seven percent hypertonic saline—0.1% hyaluronic acid in infants with mild‐to‐moderate bronchiolitis. Issue 9 (4th November 2013) - Nenna, Raffaella; Papoff, Paola; Moretti, Corrado; De Angelis, Daniela; Battaglia, Massimo; Papasso, Stefano; Bernabucci, Mariangela; Cangiano, Giulia; Petrarca, Laura; Salvadei, Serena; Nicolai, Ambra; Ferrara, Marianna; et al.
Summary Objectives Our study was aimed to evaluate the efficacy of 7% hypertonic saline and 0.1% hyaluronic acid (7% HS–HA) given by inhalation, in infants hospitalized for mild‐to‐moderate bronchiolitis. Methods In a double‐blind controlled study, 39 infants (23 boys) <7 months of age (median age 2 months) were enrolled and randomly assigned to receive either nebulized 7% HS–HA (7%NaCl + 0.1%HA) (n:21) or 0.9 normal saline (NS) (n:18) at a dose of 2.5 ml twice a day for 3 days. All infants were assigned a clinical severity score at admission and four times daily during hospitalization. Main outcome measures were number of days hospitalization, safety and daily reduction in the severity score. Results No difference was found between the two groups for clinical severity score at admission. One child in the study group and two in the NS group interrupted the study protocol; 19% of infants in the study group and 11% in the NS group had mild cough after the aerosol. The length of stay in the control group and treatment groups were 4.8 ± 1.5 versus 4.1 ± 1.9 days, respectively (P = 0.09). There was a trend for shortening the hospitalization days in the treatment group by 14.6%. The use of NS in the control group was identified as an independent risk factor for length of hospital stay using the multivariate logistic regression model (P = 0.04). No difference was observed between the two groups for the clinical score reduction during the first 3 days hospitalization. Conclusions 7% HS–HA is a safe and effective therapy in treating infants hospitalized for mild‐to‐moderate bronchiolitis. Pediatr Pulmonol. 2014; 49:919–925. © 2013 Wiley Periodicals, Inc.